Sixteen issid planthopper species in one day in Dong Son-Ky Thuong Nature Reserve in North Vietnam: Eight new species, one new genus and additional new records (Hemiptera: Fulgoromorpha: Issidae) - Constant, Jérôme; Pham, Hong Thai (European Journal of Taxonomy, 2024)
Sixteen species of Issidae (Hemiptera: Fulgoromorpha) were recorded in a single day of collecting in Dong Son-Ky Thuong Nature Reserve, Quang Ninh Province, Vietnam, of which a checklist is provided. Among them, eight species are new to science and described in different tribes and subtribes: in the Hemisphaeriini Hemisphaeriina: Gergithoides olivaceus sp. nov., Hemisphaerius bresseeli sp. nov. and Neogergithoides scapularis sp. nov.; Hemisphaeriini Mongolianina: Mongoliana vietnamica sp. nov.; Kodaianellini: Kodaianella mua sp. nov.; Parahiraciini Parahiraciina: Pusulissus quangninhensis sp. nov. and Rostrolatum curviceps sp. nov.; Sarimini: Pseudocoruncanius obliquus sp. nov. The new genus Melichergithus gen. nov. is described to accommodate Gergithus gravidus Melichar, 1906 and the new combination Melichergithus gravidus (Melichar, 1906) gen. et comb. nov. is proposed; a black form of the species is recorded for the first time and described. Two species, Longieusarima lunulia Wang, Bourgoin & Zhang, 2017 and Parallelissus fuscus Meng, Qin & Wang, 2020, are recorded from Vietnam for the first time, while another species Maculergithus luteomaculatus (Constant & Pham, 2016) is recorded for the first time from Quang Ninh Province. Four species were represented by single females that could not be identified to species level, belonging to the genera Clypeosmilus Gnezdilov & Soulier-Perkins, 2017, Fortunia Distant, 1909 (two species) and Kodaianellissus Wang, Bourgoin & Zhang, 2017. The five following genera are recorded from Vietnam for the first time: Kodaianella Fennah, 1956, Rostrolatum Che, Zhang & Wang, 2020, Longieusarima Wang, Bourgoin & Zhang, 2017, Parallelissus Meng, Qin & Wang, 2020 and Kodaianellissus. The type material of Hemisphaerius rufovarius Walker, 1858 and its junior synonyms H. scymnoides Walker, 1862, H. testaceus Distant, 1906 and H. virescens Distant, 1906 was studied and the male terminalia described; as a result, H. rufovarius is removed from the fauna of Vietnam and China. Hemisphaerius bipunctatus Melichar, 1906 is also removed from the fauna of Vietnam after examination of the corresponding specimens. This study provides a 25% increase in the number of Issidae of Vietnam; a complete list of the 51 species recorded from the country, as well as a map of the number of recorded species per province, are given and discussed.